GSK-3β inhibitory activities of novel dichroloresorcinol derivatives from Cosmospora vilior isolated from a mangrove plant. (December 2016) - Shiono, Yoshihito; Miyazaki, Nozomi; Murayama, Tetsuya; Koseki, Takuya; Harizon,; Katja, Dewa Gede; Supratman, Unang; Nakata, Juri; Kakihara, Yoshito; Saeki, Makio; Yoshida, Jun; Uesugi, Shota; et al.
Graphical abstract: Highlights: The constituents of a mangrove endophyte Cosmospora vilior were investigated. The structures of new compounds were elucidated by spectroscopic analysis. Compounds 1 and 2 inhibited Ca 2+ -signaling of mutant yeast. Compounds 1 and 2 showed GSK-3β inhibition activity. Abstract: Cosmochlorins A (1 ), B (2 ), and C (3 ) were isolated from the endophytic fungus Cosmospora vilior IM2-155. The structures of1, 2, and3 were elucidated by a combination of extensive spectroscopic analyses, including extensive 2D NMR, HRESITOFMS, and chemical reactions. Compounds1, 2, and3 were evaluated for their biological activity. Compounds1 and2 partially restored the growth inhibition caused by hyperactivated Ca 2+ -signaling in mutant yeast and showed glycogen synthase kinase (GSK)-3β inhibition activity at IC50 values of 62.5 and 60.6 μM, respectively. Further, compound2 significantly increased osteoclast formation by more than 1.5-fold in RAW264.7 cells compared to receptor activator of nuclear factor-κB ligand (RANKL) alone.